PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PARAGITA TUNAS INSPIRA WARDAH DC JAKARTA - Oriza Syifadila Zein; Angga Rovita (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of training and work discipline on employee performance at PT Paragita Tunas Inspira, a company under the auspices of PT Paragon Technology and Innovation. The background of this research is the importance of improving human resource quality through continuous training and the implementation of work discipline in order to enhance employee performance. This research uses a quantitative approach, with data collected through questionnaires distributed to 75 employee respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, t-test, F-test, correlation coefficient analysis, and coefficient of determination (R²), with the assistance of SPSS version 26. The results show that partially, the training variable (X1) has a positive and significant effect on employee performance (Y), as indicated by a t- value of 11.486 > t-table 1.993 and a significance value of 0.000 < 0.05. Furthermore, the work discipline variable (X2) also has a positive and significant effect on employee performance, with a t-value of 24.556 > t-table 1.993 and a significance value of 0.000 < 0.05. Simultaneously, training and work discipline have a positive and significant effect on employee performance, as evidenced by an F-value of 327.352 with a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.901 indicates that 90.1% of the variation in employee performance is influenced by training and work discipline, while the remaining 9.9% is influenced by other factors outside this study.Therefore, it can be concluded that training and work discipline play an important role in improving employee performance at PT Paragita Tunas Inspira. Thus, the company is expected to continuously improve the quality of training programs and consistently enforce work discipline to achieve optimal employee performance.